PENGARUH KOMPLEKSITAS TUGAS, LOCUS OFF CONTROL, TEKANAN KETAATAN, SIKAP PROFESIONALISME DAN GENDER TERHADAP AUDIT JUDGMENT (Studi Empiris Pada Kantor Akuntan Publik di Kota Semarang) - Emily Wijaya, 14.05.52.0005; Himmawan D. N, Arief (Students' Journal of Accounting and Banking, 2018)
A good audit quality can be generated by the auditor by instilling independence and competence in the audit of financial statements. This is based on the application of public accountant code of ethics as a basic principle that regulates the ethics of the public accounting profession, in addition to the time budget pressure, an auditor will be able to improve the quality of his work. Audit quality is influenced by various factors such as independence, competence, time budget pressure and auditor ethics. This study aims to examine the influence of independence, competence and time budget pressure on audit quality with auditor ethics as a moderation variable. The population in this study is all auditors from the level of partners, managers, senior and junior working in Public Accounting Firm (KAP) in Central Java and Yogyakarta Special Region (DIY). Sampling technique using convenience sampling and obtained a sample of 65 respondents. The method of collecting primary data was conducted through survey method using questionnaire. The data obtained were analyzed using multiple linear regression model and using residual test to test the effect of moderation variable through SPSS 21.0. The results of this study indicate that the competence and time budget pressure have a positive effect on audit quality while independence has no positive effect on audit quality. The auditor ethics moderates the influence of independence, competence and time budgetary pressures on audit quality. Keywords: independence, competence, time budget pressure, auditor ethics and audit quality.